Electrophysiological investigation of intact retina with soft printed organic neural interface - Vėbraitė, Ieva; David-Pur, Moshe; Rand, David; Głowacki, Eric Daniel; Hanein, Yael (Journal of neural engineering, 2021)
Objective.Understanding how the retina converts a natural image or an electrically stimulated one into neural firing patterns is the focus of on-going research activities.Ex vivo, the retina can be readily investigated using multi electrode arrays (MEAs). However, MEA recording and stimulation from an intact retina (in the eye) has been so far insufficient.Approach.In the present study, we report new soft carbon electrode arrays suitable for recording and stimulating neural activity in an intact retina. Screen-printing of carbon ink on 20µm polyurethane (PU) film was used to realize electrode arrays with electrodes as small as 40µm in diameter. Passivation was achieved with a holey membrane, realized using laser drilling in a thin (50µm) PU film. Plasma polymerized 3.4-ethylenedioxythiophene was used to coat the electrode array to improve the electrode specific capacitance. Chick retinas, embryonic stage day 13, both explanted and intact inside an enucleated eye, were used.Main results.A novel fabrication process based on printed carbon electrodes was developed and yielded high capacitance electrodes on a soft substrate.Ex vivoelectrical recording of retina activity with carbon electrodes is demonstrated. With the addition of organic photo-capacitors, simultaneous photo-electrical stimulation and electrical recording was achieved. Finally, electrical activity recordings from an intact chick retina (inside enucleated eyes) were demonstrated. Both photosensitive retinal ganglion cell responses and spontaneous retina waves were recorded and their features analyzed.Significance.Results of this study demonstrated soft electrode arrays with unique properties, suitable for simultaneous recording and photo-electrical stimulation of the retina at high fidelity. This novel electrode technology opens up new frontiers in the study of neural tissuein vivo.
Keywords: mikroelektrody; microelectrodes; neuro-stimulation; soft neural interfaces; retina; Retina; Electric Stimulation; neural prosthesis; elektrická stimulace; Microelectrodes